High Density 3D Carbon Tube Nanoarray Electrode Boosting the Capacitance of Filter Capacitor - Chen, Gan; Han, Fangming; Ma, Huachun; Li, Pei; Zhou, Ziyan; Wang, Pengxiang; Li, Xiaoyan; Meng, Guowen; Wei, Bingqing (Nano-Micro Letters, 2024)
Electric double-layer capacitors (EDLCs) with fast frequency response are regarded as small-scale alternatives to the commercial bulky aluminum electrolytic capacitors. Creating carbon-based nanoarray electrodes with precise alignment and smooth ion channels is crucial for enhancing EDLCs’ performance. However, controlling the density of macropore-dominated nanoarray electrodes poses challenges in boosting the capacitance of line-filtering EDLCs. Herein, a simple technique to finely adjust the vertical-pore diameter and inter-spacing in three-dimensional nanoporous anodic aluminum oxide (3D-AAO) template is achieved, and 3D compactly arranged carbon tube (3D-CACT) nanoarrays are created as electrodes for symmetrical EDLCs using nanoporous 3D-AAO template-assisted chemical vapor deposition of carbon. The 3D-CACT electrodes demonstrate a high surface area of 253.0 m2 g−1, a D/G band intensity ratio of 0.94, and a C/O atomic ratio of 8. As a result, the high-density 3D-CT nanoarray-based sandwich-type EDLCs demonstrate a record high specific areal capacitance of 3.23 mF cm−2 at 120 Hz and exceptional fast frequency response due to the vertically aligned and highly ordered nanoarray of closely packed CT units. The 3D-CT nanoarray electrode-based EDLCs could serve as line filters in integrated circuits, aiding power system miniaturization. Highlights: 1 A novel method is developed for precise control over the structure of 3D anodic aluminum oxide templates, enabling fine-tuning of both the vertical pore diameter and interspace within the templates. 2 3D carbon tube nanoarrays featuring significantly thinner and denser tubes are constructed as high-quality electrodes for miniaturized filter capacitors. 3 The 3D compactly arranged carbon tube-based capacitor achieves a remarkable specific areal capacitance of 3.23 mF cm−2 with a phase angle of − 80.2° at 120 Hz.